Pediatric hypertension: a toolkit for optimizing lifestyle and pharmacologic adherence - Aaron Walsh; Thomas Yohannan; Evan Harvey; Arif Hussain; Nirbhay Parashar; Deepank Sahni; Carmen Carroll; Ranjit Philip (Exploration of Medicine)
Hypertension (HTN) has significant long-term cardiovascular risks and is becoming increasingly prevalent in the pediatric population. Apart from making the diagnosis of HTN and initiating treatment, sustained adherence to lifestyle modifications is the mainstay of pediatric HTN management. Little is described regarding compliance to lifestyle recommendations as treatment for HTN despite current guidelines outlining specific dietary and physical activity recommendations that are suggested to be equated to medical prescriptions. This is possibly because there are more objective metrics such as pharmacy pick-up/refill data that can more accurately track medication compliance. The purpose of this review is to provide the general pediatrician with a standardized framework for the management of pediatric HTN with a focus on objective tools that will enable a pragmatic approach to evaluating patient compliance. Adherence to lifestyle modifications focusing on diet and physical activity may potentially impact blood pressure control beyond drug therapy compliance. Concise flowsheets and tables are provided to aid the pediatrician’s workflow in a busy clinic whilst providing essential objective data to assess patient compliance and provide nutrition and physical activity prescriptions. In this review, we outline our current understanding of lifestyle modification and medication prescription compliance trends among youths with HTN and offer real-world tools to implement in any pediatric clinic to better understand and improve patient compliance.